Nano-tailoring of infiltrated catalysts for high-temperature solid oxide regenerative fuel cells - Yoon, Kyung Joong; Biswas, Mridula; Kim, Hyo-Jin; Park, Mansoo; Hong, Jongsup; Kim, Hyoungchul; Son, Ji-Won; Lee, Jong-Ho; Kim, Byung-Kook; Lee, Hae-Weon (ELSEVIER SCIENCE BV, 2017)
Solid oxide regenerative fuel cells (SORFCs), which perform the dual functions of power generation and energy storage at high temperatures, could offer one of the most efficient and environmentally friendly options for future energy management systems. Although the functionality of SORFC electrodes could be significantly improved by reducing the feature size to the nanoscale, the practical use of nanomaterials has been limited in this area due to losses in stability and controllability with increasing temperature. Here, we demonstrate an advanced infiltration technique that allows nanoscale control of highly active and stable catalysts at elevated temperatures. Homogeneous precipitation in chemical solution, which is induced by urea decomposition, promotes crystallization behavior and regulates precursor redistribution, thus allowing the precise tailoring of the phase purity and geometric properties. Controlling the key characteristics of Sm0.5Sr0.5CoO3 (SSC) nanocatalysts yields an electrode that is very close to the ideal electrode structure identified by our modeling study herein. Consequently, outstanding performance and durability are demonstrated in both fuel cell and electrolysis modes. This work highlights a simple, cost-effective and reproducible way to implement thermally stable nanocomponents in SORFCs, and furthermore, it expands opportunities to effectively exploit nanotechnology in a wide range of high-temperature energy devices.
Keywords: YTTRIA-STABILIZED ZIRCONIA; HIGH-PERFORMANCE CATHODE; COMPOSITE CATHODES; IMPREGNATION METHOD; REACTION-MECHANISM; AIR ELECTRODE; SOFC; FABRICATION; MODEL; POLARIZATION